Effect of hormonal contraceptives on the ocular surface and the tear film - Muhammad Syauqie (Universitas Gadjah Mada, 2022)
Dry eye syndrome (DES) is a common multifactorial disease of the tears andocular surface associated with sex hormones. Hormonal contraception is arisk factor for DES, but its relationship with DES exacerbations in womenof childbearing age is still unclear. This study aimed to evaluate changesof the tear film and ocular surface of young women using the hormonalcontraceptive agent. It was a case-control study involving 56 healthywomen aged 20 to 45 y.o. Subjects was divided into two groups i.e. thehormonal contraceptives group and the control group without hormonalcontraceptive. Subjects were interviewed with the ocular surface diseaseindex (OSDI) questionnaire. Tear secretion and tear stability were measuredusing Schirmer’s I test and fluorescein tear break-up time test (TBUT).Ocular surface impression cytology with cellulose acetate filter paper wastaken from inferonasal bulbar conjunctiva and was stained with periodicacid- Schiff (PAS) and counterstained with hematoxylin and eosin (HE). Nosignificantly decrease in tear secretion and tear stability in the hormonalcontraceptives group compared with the control groups was observed (p >0.05). However, a statistically significant decrease in goblet cell density andconjunctival epithelium metaplasia was observed, where 25% of the hormonalcontraceptives group had an abnormal impression cytology result comparedwith the control group (p<0.05). The hormonal contraceptives group also hada higher OSDI score than the control group, although it was not statisticallysignificant (p> 0.05). The hormonal contraceptives group had a signifificanteffect on the ocular surface in which it induced squamous metaplasia andinflflammation of conjunctival cells and the reduced number of goblet cellsp<0.05). The slightly decreased tear film volume and stability accompaniedby an increase in OSDI score found in the hormonal contraceptives groupsupport the possibility of hormonal contraceptive use as one of the riskfactors in the occurrence of dry eye syndrome.